2019
DOI: 10.7759/cureus.6008
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Impact on Aesthetic Procedures Among Females in Riyadh, Saudi Arabia

Abstract: Aesthetic procedures represent one of the most commonly performed procedures in the medical field. Such procedures have been growing in popularity. Social media is a term used to describe electronic platforms that promote the dissemination of information to targeted users. These platforms play a critical role in promoting aesthetic procedures.ObjectiveThe objective of this study was to assess the impact of social media on aesthetic procedures among the female population in Riyadh, Saudi Arabia.MethodsA cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 12 publications
7
26
0
Order By: Relevance
“…Aesthetic procedures are among the most commonly performed surgeries in the medical field. These procedures have been growing in popularity in our nation due to multiple factors including body image dissatisfaction and the pursuit of perfection, in addition to the growing influence of social media [ 1 ]. Cosmetic surgery focuses on enhancing appearance including surgical procedures such as blepharoplasty, rhinoplasty, and breast augmentation, as well as nonsurgical procedures, such as chemical peels and botulinum toxin injections.…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetic procedures are among the most commonly performed surgeries in the medical field. These procedures have been growing in popularity in our nation due to multiple factors including body image dissatisfaction and the pursuit of perfection, in addition to the growing influence of social media [ 1 ]. Cosmetic surgery focuses on enhancing appearance including surgical procedures such as blepharoplasty, rhinoplasty, and breast augmentation, as well as nonsurgical procedures, such as chemical peels and botulinum toxin injections.…”
Section: Introductionmentioning
confidence: 99%
“…Alghamdi et al in their work reported that social media applications in general and Snapchat in specific had a huge impact on the decision to undergo rhinoplasty [16]. On the other hand, Alghonaim et al [17], Park et al [18], and AlAlshaalan et al [19] stated that the platform with the greatest influence on the perception and decision to undergo aesthetic procedures was Instagram. Aldosari et al [20] in their work reported they the majority of patients seeking consultation in plastic surgery clinics were impacted by the before and after photos, they encountered on social media.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Saudi Arabia polled 1,449 patients at a facial plastic surgery clinic; a profound 68% of these patients cited that their decision to receive treatment was influenced, in some way, by social media. 13 Another group recently analyzed social media trends with patients’ interest in cosmetic procedures and found that online interest in noninvasive cosmetic procedures is also increasing, largely because of social media. 14 These researchers focused on dermatological cosmetic medicine, citing a growing online interest in this field as well.…”
Section: Discussionmentioning
confidence: 99%